1998
DOI: 10.1016/s0092-8674(00)81695-5
|View full text |Cite
|
Sign up to set email alerts
|

Y Do We Drink?

Abstract: the regulation of mammalian responses to alcohol. Spe-* Department of Psychiatry and cifically, Thiele et al. (1998) show that genetic manipula-Center for Neurobiology and Psychiatry tions that alter the levels of NPY in mice affect the sensi- † Departments of Anatomy and Neurology tivity of these animals to the sedative effects of ethanol and the Gallo Center as well as their preference for ethanol. We consider ‡ Program in Neuroscience these observations in the context of proposed roles for § Program in Deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Therefore, the relationship between NPY and the alcoholism risk continues to be worth consideration, with the possibility that genes for specific receptors [e.g., NPY5C (Schroeder et al, 2004)] might prove to be more important for LR. It is also possible that NPY-related genes could have an impact on the alcoholism risk through a separate mechanism, such as higher rates of anxiety symptoms (Pandey et al, 2003;Schuckit, 2002;Tecott and Heberlein, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the relationship between NPY and the alcoholism risk continues to be worth consideration, with the possibility that genes for specific receptors [e.g., NPY5C (Schroeder et al, 2004)] might prove to be more important for LR. It is also possible that NPY-related genes could have an impact on the alcoholism risk through a separate mechanism, such as higher rates of anxiety symptoms (Pandey et al, 2003;Schuckit, 2002;Tecott and Heberlein, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A third gene that has been linked to alcohol consumption in some studies and that may contribute to LR is neuropeptide Y (NPY), an inhibitory neuropeptide that couples with G proteins and inhibits the production of cyclic AMP (Schroeder et al, 2004;Thiele et al, 2000). NPY-deficient mice have elevated alcohol intake and lower LR, whereas transgenic mice with higher NPY have the opposite alcohol-related profile (Tecott and Heberlein, 1998;Thiele et al, 2000). Leu7Pro, a missense variant in the signal peptide of the human prepro NPY (Karvonen et al, 1998), affects the intracellular processing of the prepro NPY and the subsequent release of the mature peptide (Kallio et al, 2001).…”
mentioning
confidence: 99%
“…For example, the expression of neuropeptide Y (NPY), was decreased significantly in the alcoholic case groups and NPY is a major neuromodulator in the brain and is expressed at high levels in regions involved in motivation and emotion. NPY is known to control feeding and stress responses (Levine and Morley 1984;Heilig et al 1993) and has been shown to play a role in alcohol consumption (Tecott and Heberlein 1998;Li 2000). This neuropeptide has also been implicated in mediating alcohol intake in rats selected for high and low alcohol preference (Ehlers et al 1998;Caberlotto et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, one group at relatively low future risk for alcoholism, Jewish subjects, demonstrated a significantly higher intensity of response to alcohol in an alcohol challenge (Monteiro et al, 1991). Data from most relevant animal studies also indicate a relationship between a lower intensity of response to alcohol and the consumption of higher doses of alcohol in experimental situations (Baldwin et al, 1991;Barr et al, 2004;Crabbe et al, 1996;Tecott and Heberlein, 1998). Further support for the importance of LR as a risk factor for heavier drinking, alcohol-related problems, and AUDs comes from the demonstration in both animal models and human studies of a heritability for LR estimated to be between .40 and .60.…”
Section: Introductionmentioning
confidence: 96%